Urban Space Transformation In Medan Johor District The Influence Of Elite Housing Development On Spatial Patterns - Anindya Sofira, Disha (International Journal of Architecture and Urbanism, 2025)
Urban space transformation is meant as the processes of change in the form of urban space that always experiences changes in each phase of development. Transformation always begins with the emergence or development of settlement elements at a certain time, then finally experiences changes over a certain period of time. Observations were Observations were made on residential areas in Medan Johor District which in recent decades have shown developments that have an impact on changes in spatial patterns in the area. The study aims to determine the transformation of urban space in elite housing on spatial patterns in Medan Johor District using descriptive-qualitative research methods. The results of the conclusion of this study show the development of elite housing on spatial patterns in Medan Johor District in 2024, precisely in the housing that has been studied, it can be said that the land has expanded. Housing that was previously empty land in 2017, in 2022 has experienced quite rapid regional development